Inkjet Conductive Inks for Printing Textile Materials and Applications (Journal of Fiber Bioengineering and Informatics, 2019)
The inkjet printing technique has been rapidly developing for the realization of flexible electronic devices.The antennas, sensors and transistors have been successfully introduced on flexible substrates such asglass, silicone and many films. Since the inkjet printing technique is a direct writing process, thebenefits include flexible design, low-cost and environmentally friendly. It is also possible to create a highresolution of printed lines. Therefore, this technique is believed to have a great potential for applying ontextile substrates. However, the challenge is to ensure that the small droplets can penetrate through thethickness of the fabric in order to spread along the threads. Thus, the uniformity and continuity are notacceptable for practical applications. This paper summarises inkjet printing technologies and potentialapplications on textile substrates.
Keywords: Ink Jet Printers; Conductive Material; Smart Fabrics